К вопросу о связях восточного Закавказья и Ирана в конце II - начале I тыс. до н. э. - Погребова, M. H.
Pogrebova, M. N.; On Relations between Eastern Transcaucasia and Iran at the Turn of the First Millenium B.C.; engl. Résumé S. 342.